Silibinin downregulates the NF-κB pathway and NLRP1/NLRP3 inflammasomes in monocytes from pregnant women with preeclampsia - Matias, Mariana Leticia [UNESP] (2019)
Preeclampsia (PE) is a human pregnancy-specific syndrome with abnormal activation of cells from the innate immune system. The present study evaluated whether silibinin (SB) treatment of monocytes from preeclamptic women could modulate NLRP1 and NLRP3 inflammasomes as well as TLR4/NF-κB pathway activation. Peripheral blood monocytes from 20 preeclamptic and 20 normotensive (NT) pregnant women, as well as the THP-1 cell line, were cultured with or without monosodium urate (MSU) or SB. NLRP1, NLRP3, Caspase-1, TLR4, MyD88, NF-κB, IL-1β, IL-18, TNF-α and IL-10 gene expression by monocytes was analysed by quantitative real-time polymerase chain reaction (qPCR), while inflammatory cytokine production and p65NF-κB activity were determined by enzyme-linked immunosorbent assays (ELISAs). TLR4/MyD88/NF-κB and NLRP1/NLRP3 inflammasomes pathways in THP-1 cells were evaluated by flow cytometry and western blot respectively. Compared with NT women, monocytes from preeclamptic women showed The Ethics Committee of the Botucatu Medical School approved the study (protocol number 2.333.216)higher endogenous activation of NLRP1/NLRP3 inflammasomes and the TLR4/NF-κB pathway as well as higher gene and protein expression of IL-1β, IL-18 and TNF-α, and lower expression of IL-10. Monocyte stimulation with MSU increased inflammation-related genes as well as NF-κB activity. In vitro, SB treatment of monocytes from preeclamptic women reduced the basal activation of these cells by decreasing NLRP1/NLRP3 inflammasomes and p65NF-κB activity. THP-1 cells exhibited a similar immunological response profile to monocytes from preeclamptic women when cultured with or without MSU or SB. These results suggest uric acid participates in the systemic inflammatory response characteristic of preeclampsia and that in vitro SB treatment can modulate the sterile inflammation established in monocytes from preeclamptic women.